2018
DOI: 10.1002/adem.201700863
|View full text |Cite
|
Sign up to set email alerts
|

Impact Toughness of Ultrafine‐Grained Commercially Pure Titanium for Medical Application

Abstract: This study aims at achieving the best combination of strength, ductility, and impact toughness in ultrafine-grained (UFG) Ti Grade 4 produced by equalchannel angular pressing via Conform scheme (ECAP-C) with subsequent cold drawing. UFG structures with various parameters (e.g., size and shape of grains, dislocation density, conditions of boundaries) are formed by varying the treatment procedures (deformation temperature and speed at drawing, annealing temperature). The tensile and impact toughness tests were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In the range of 450-500°C (0.37-0.39 Tm) the material softened noticeably. This effect has also been found previously during annealing of severely-deformed titanium and has been usually attributed to recrystallization [4,8,9,10]. A further increase in annealing temperature to 600°C (0.44 Tm) resulted in a gradual softening followed by a slight strength increase at higher temperatures.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In the range of 450-500°C (0.37-0.39 Tm) the material softened noticeably. This effect has also been found previously during annealing of severely-deformed titanium and has been usually attributed to recrystallization [4,8,9,10]. A further increase in annealing temperature to 600°C (0.44 Tm) resulted in a gradual softening followed by a slight strength increase at higher temperatures.…”
Section: Resultssupporting
confidence: 80%
“…Moreover, a remarkable hardening effect is sometimes observed in this temperature range [3][4][5][6]. On the other hand, a further increase of the annealing temperature to 400oC usually leads to material softening and essential restoration of ductility [4,[7][8][9][10], thus evidencing a recovery process [10]. Recrystallization of SPD CP Ti is often found to occur within the temperature interval of 400-500°C [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dependence of the impact strength K CV on the uniform elongation δ u of UFG Grade 4 Ti samples. Reproduced with permission . 2018, John Wiley and Sons.…”
Section: Advanced Properties Of Ufg Titanium Alloysmentioning
confidence: 99%
“…Since the plane strain fracture toughness ( K IC ) and impact toughness (CVN) are both used to express material toughness, it appears paradoxical about the variation of them. Several investigations demonstrated that the grain size, second phase, and grain boundary have different effects on the impact toughness and fracture toughness. Ritchie et al emphasized that the contradictory result of the toughness appear to be an indeed indication of important difference between fracture induced by the critical cleavage stress and characteristic distance.…”
Section: Introductionmentioning
confidence: 99%